Variable Temperature NMR Experiment Studying Cyanopyridone Structure - Thu, Bui Thai Thanh; Hung, Mac Dinh; Trung, Pham Quang (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 1, 2023)
In this study, we describe the NMR  1 H-NMR, JMOD- 13 C-NMR và HSQC at variable temperatures to determine the structure of the pyridone compound with specific conformation which cause the unavailable of signal at 298K. Experiment of different NMR spectrum at variable temperatures helps to confirm the structure of the product of a three-component reaction.